The Orthodox Church and Religious Minorities in Shida Kartli Region in Georgia in the First Quarter of the Twentieth Century - Sosiashvili, Giorgi (Occasional papers on religion in Eastern Europe, 2017)
"We think that it is of utmost importance to disclose the facts about the uncommon treatment that took place during Soviet rule in the 1920s towards the Georgian Orthodox Church and all the other religious confessions."